Reliability of Stochastic Stress-Strength Models - Swathi, Nalabolu (Cambridge Scholars Publisher, 2020)
This volume explores the reliability of time-dependent models using a variety of different concepts and techniques it details. It will be useful for research-level courses in statistics, applied mathematics, and operations research. The book will also be of interest to researchers requiring knowledge of applied probability and applied stochastic processes.